Identifikasi Sumber Risiko pada Penanganan Pascapanen Baby Buncis Kualitas Ekspor di PT. Asia Agro - Markhamah, Nadya Julia; Aditiawati, Pingkan; Rosmiati, Mia (Universitas Galuh, 2025)
Baby beans are one of Indonesia's export commodities, and one of their production centres is located in West Java, Lembang district. PT Asia Agro, a company engaged in horticultural export, cooperates with farms in Lembang Subdistrict to export baby beans. Like any other business, the post-harvest activities of baby beans have risks that potentially reduce the profits earned by PT Asia Agro. The existence of various risks requires an analysis of the sources of risk. This research was conducted with the aim of identifying different risk events in the post-harvest handling of baby beans and analysing the dominant risks. This research is a case study of Asia Agro, with qualitative descriptive analysis to explain the description of the business risks and quantitative analysis using House of Risk I to calculate the risks. Based on the research, Asia Agro's risk events were identified in the form of poor-quality products from suppliers, errors in the grading and packing process, quality degradation during temporary storage, and product damage at the export destination. In addition, there are 19 sources of risk, of which 10 are dominant, including successively from the first to the fifth order, namely: pests and diseases handling in the field is not optimal (14.50%), transportation of products using plastic or sacks (10.72%), products exposed to excessive heat during transport to the packing house (9.99%), sorting errors (9.73%), and errors during harvesting (6.71%). With 64.48%, the dominant risk is the production aspect, and 35.52% is included in the human resources aspect.